ChemInform Abstract: Metal‐Catalyzed Isomerization of Allylic and Propargylic Alcohols in Aqueous Media. Issue 36 (15th August 2013) - Garcia‐Alvarez, Joaquin; Garcia‐Garrido, Sergio E.; Crochet, Pascale; Cadierno, Victorio
Abstract Review: 177 refs.